Essential Research Findings / In Counselling and Psychotherapy - Cooper Mick (Bacp, 2008)
This book sets out the evidence for the effectiveness of therapy in an entirely jargon-free way. Foreword, Acknowledgements, Introduction: The Challenge of Research, The Outcomes of Counselling and Psychotherapy, Does Orientation Matters? The Great Psychotherapy Debate, Client Factors: The Heart and Soul of Therapeutic Change, Therapist Factors: Who Works for That?, Relational Factors: It's the Relationship that Heals...or Is It?, Technique and Practice Factors: Is It What You Do or the Way That You Do It?, Conclusion, Appendix: The Efficacy and Effectiveness of Different Therapeutic Orientations, Glossary, Research Quiz Answers, References, Name and Subject Index.